Full-mouth rehabilitation of an oral scleroderma patient with implant-fixed prostheses - Miss Jo Jisu (Elsevier, 2023)
Introduction: Chronic graft versus host disease(cGVHD) is one of the common complications after hematopoietic stem cell transplantation. This occurs when the transfused lymphocytes cannot be destroyed by the host's immune mechanism. This case reports the full-mouth rehabilitation using implant-fixed prostheses in a patient with cGVHD, with satisfactory results. Case Description: A 50-year-old male patient was referred from the Department of Hematology for chewing difficulty. He was diagnosed with acute myeloid leukemia, and underwent allogeneic hematopoietic stem cell transplantation and cGVHD emerged afterwards. Limited mouth opening due to scleroderma was observed and all residual teeth were involved in dental caries. A treatment plan was established with extraction of all remaining teeth and full-mouth rehabilitation with implant-fixed prostheses. We decided to place 14 implants in the maxilla and mandible. The positions of the dental implants were 16, 14, 13, 11, 21, 23, 24, 26, 33, 34, 36, 43, 44, and 46 according to the Fédération Dentaire International (FDI) two-digit system. After 4 months of osseointegration period, impression was taken using a transfer coping and stock tray with polyvinylsiloxane material. The final prostheses were made of monolithic zirconia, except for the maxillary anterior teeth made of porcelain fused to gold in consideration of esthetics. Careful occlusal adjustment was done to provide bilateral occlusion and mutually protected occlusion in lateral movement. Discussion: In this case, the cGVHD patient demonstrated acceptable marginal bone resorption and good soft tissue condition at 2-year follow-up after full mouth rehabilitation with implant-fixed prostheses. Conclusion/Clinical Significance: Implant-supported prostheses may be a viable treatment for patients with oral scleroderma caused by cGVHD.